Crypto Mining as a Threat to Energy and the Environment from the Perspective of Criminal Law Reform - Fernando, Zico Junius; Arifin , Firdaus; Sunggara, Muhamad Adystia; Muthia, Arini Azka (Jurnal Media Hukum, 2025)
The rapid growth of cryptocurrency mining has led to significant environmental and energy concerns worldwide. Bitcoin mining alone consumes more than 170 TWh of electricity annually, equivalent to the energy consumption of countries like Poland or Malaysia, and generates nearly 98 million tons of CO₂ emissions. These impacts have prompted stringent global responses, such as China’s nationwide ban on cryptocurrency mining in 2021 and the European Union’s requirement for environmental disclosures from cryptocurrency service providers. In Indonesia, however, regulations remain unclear and fragmented. Current environmental and criminal laws do not yet explicitly address the ecological harm caused by cryptocurrency mining, including high electricity consumption, electronic waste, and unauthorized power connections. As a result, many mining activities operate in a legal vacuum without accountability. This study identifies these legal gaps and proposes reforms combining preventive regulation, corporate criminal liability, environmental transparency, and community-oriented sanctions to strengthen ecological justice and constitutional environmental protection.